2021
DOI: 10.3390/su13094785
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Green Development in Dongliao River Basin from the Integration System of “Multi-Dimensions”

Abstract: The bottlenecks in enhancing regional green development are resource shortages, environmental pollution, and ecological degradation. Taking the Dongliao River Basin (DRB) of Jilin Province as an example, this study explored green development from a multidimensional perspective. Based on the dimension evaluation results of REECC (resources, environment, and ecological carrying capacity), PLES (production–living–ecological space), and ER (ecological redline), the coupling coordination degree model and spatial au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This paper answered the above questions through basic facts, theoretical analysis, and empirical tests. The marginal contributions are from the following three aspects: (1) We used a comprehensive index system to measure the development level of green finance rather than a single index, since China's green financial system is developing rapidly, involving securities, insurance, credit, and other fields [15]. According to the framework of green finance development in China, green credit, green securities, green investment, and green insurance are taken as the four indicators in this paper to measure the development level of green finance in Chinese 30 provinces.…”
Section: Introductionmentioning
confidence: 99%
“…This paper answered the above questions through basic facts, theoretical analysis, and empirical tests. The marginal contributions are from the following three aspects: (1) We used a comprehensive index system to measure the development level of green finance rather than a single index, since China's green financial system is developing rapidly, involving securities, insurance, credit, and other fields [15]. According to the framework of green finance development in China, green credit, green securities, green investment, and green insurance are taken as the four indicators in this paper to measure the development level of green finance in Chinese 30 provinces.…”
Section: Introductionmentioning
confidence: 99%
“…Exploratory spatial analysis techniques can analyze the spatial correlation of GDE. The spatial clustering characteristics of GDE have been demonstrated in many studies [26,27], which indicates that green development levels between neighboring regions tend to be similar, implying a spatial spillover effect of its efficiency. Other studies have indicated that economic, financial, urbanization and resource utilization can drive the green development level of surrounding areas through spillover effects [28][29][30], thus establishing clustered green development.…”
Section: Introductionmentioning
confidence: 84%
“…Jiang used indicators such as energy consumption per unit of GDP and pollution status in the study of green development level in the Shandong Peninsula urban agglomeration [31]. Wang used indicators such as environmental pollution and ecological space in the comprehensive evaluation of green development in the Dongliao River Basin [32]. Yue used indicators such as personnel efficiency, economy, and environmental impact in the evaluation of green development efficiency in resource-based cities in the Yellow River Basin [33].…”
Section: Construction Of An Evaluation Model For Rural Green Developm...mentioning
confidence: 99%